Foreword to the special virtual issue on X-ray spectroscopy to understand functional materials: instrumentation, applications, data analysis - Elisa Borfecchia; Kirill A. Lomachenko; Kristina Kvashnina (Journal of Synchrotron Radiation)
Foreword to the virtual focused issue of Journal of Synchrotron Radiation on X-ray spectroscopy to understand functional materials: instrumentation, applications, data analysis.